Claims in vapour device (e-cigarette) regulation: A Narrative Policy Framework analysis - O'Leary, R.; Borland, R.; Stockwell, Tim; MacDonald, M. (Elsevier BV, 2017)
Background: The electronic cigarette or e-cigarette (vapour device) is a consumer product undergoing rapid growth, and governments have been adopting regulations on the sale of the devices and their nicotine liquids. Competing claims about vapour devices have ignited a contentious debate in the public health community. What claims have been taken up in the state arena, and how have they possibly influenced regulatory outcomes? Methods: This study utilized Narrative Policy Framework to analyze the claims made about vapour devices in legislation recommendation reports from Queensland Australia, Canada, and the European Union, and the 2016 deeming rule legislation from the United States, and examined the claims and the regulatory outcomes in these jurisdictions. Results: The vast majority of claims in the policy documents represented vapour devices as a threat: an unsafe product harming the health of vapour device users, a gateway product promoting youth tobacco uptake, and a quasi-tobacco product impeding tobacco control. The opportunity for vapour devices to promote cessation or reduce exposure to toxins was very rarely presented, and these positive claims were not discussed at all in two of the four documents studied. Conclusion: The dominant claims of vapour devices as a public health threat have supported regulations that have limited their potential as a harm reduction strategy. Future policy debates should evaluate the opportunities for vapour devices to decrease the health and social burdens of the tobacco epidemic.